Odpowiedź :
Odpowiedź:
[tex]a)\ \ \sqrt{432}=\sqrt{2\cdot2\cdot2\cdot2\cdot3\cdot3\cdot3}=\sqrt{2^4\cdot3^2\cdot3}=\sqrt{16\cdot9\cdot3}=4\cdot3\sqrt{3}=12\sqrt{3}\\\\\\b)\ \ \sqrt{448}=\sqrt{2\cdot2\cdot2\cdot2\cdot2\cdot2\cdot7}=\sqrt{2^6\cdot7}=\sqrt{64\cdot7}=8\sqrt{7}\\\\\\c)\ \ \sqrt{864}=\sqrt{2\cdot2\cdot2\cdot2\cdot2\cdot3\cdot3\cdot3}=\sqrt{2^4\cdot2\cdot3^2\cdot3}=\sqrt{16\cdot9\cdot6}=4\cdot3\sqrt{6}=\\\\=12\sqrt{6}[/tex]
[tex]d)\ \ \sqrt{972}=\sqrt{2\cdot2\cdot3\cdot3\cdot3\cdot3\cdot3}=\sqrt{2^2\cdot3^4\cdot3}=\sqrt{4\cdot81\cdot3}=2\cdot9\sqrt{3}=18\sqrt{3}\\\\\\e)\ \ \sqrt[3]{432}=\sqrt[3]{2\cdot2\cdot2\cdot2\cdot3\cdot3\cdot3}=\sqrt[3]{2^3\cdot2\cdot3^3}=2\cdot3\sqrt[3]{2}=6\sqrt[3]{2}\\\\\\f)\ \ \sqrt[3]{1375}=\sqrt[3]{5\cdot5\cdot5\cdot11}=\sqrt[3]{5^3\cdot11}=5\sqrt[3]{11}[/tex]
[tex]g)\ \ \sqrt[3]{-375}=-\sqrt[3]{375}=-\sqrt[3]{3\cdot5\cdot5\cdot5}=-\sqrt[3]{3\cdot5^3}=-5\sqrt[3]{3}\\\\\\h)\ \ \sqrt[3]{-3645}=-\sqrt[3]{3645}=\sqrt[3]{3\cdot3\cdot3\cdot3\cdot3\cdot3\cdot5}=-\sqrt[3]{3^3\cdot3^3\cdot5}=-3\cdot3\sqrt[3]{5}=\\\\=-9\sqrt[3]{5}[/tex]